Exploration of attendance, active Participation, and behavior change in a group-based responsive stimulation, maternal and child health, and nutrition intervention - Yeasmin, Farzana; Winch, Peter J.; Hwang, Sharon T.; Leontsini, Elli; Jahir, Tania; Das, Jyoti B.; Amin, Mohammad R.; Hossain, Md K.; Huda, Tarique Md. Nurul; Akter, Fahmida; Shoab, Abul Kashem; Tofail, Fahmida; et al. (ASTMH, 2022)
This article was published in The American Journal of Tropical Medicine and Hygiene [© The American Society of Tropical Medicine and Hygiene 2021] and the definite version is available at: https://doi.org/10.4269/ajtmh.20-0991 The Journal's website is at: https://www.ajtmh.org/view/journals/tpmd/104/4/article-p1586.xml